Developing Primary Liaison Psychiatric Services for HIV/AIDS Patients in Community - Ahsan Ahsan; Retno Lestari (International Journal of Public Health Science (IJPHS), 2017)
In Indonesia, the number of HIV/AIDS patients has grown at significant level. HIV can be a source of major stress which can lead to changes in mental health, such as persistent sadness, feeling empty and anxiety. The ability of liaison officer could help patients reduce their psychiatric problems and at the same time it can greatly affect patients' risks for transmission of HIV to others. This study aimed to analyze the effect of developing primary liaison psychiatric services for HIV/AIDS patients on the abilities of health care workers to provide treatments. This study used a quasi experimental design with one group pretest-posttest which included 64 health care workers aged between 20 and 50 years from the Community-Integrated Health Care in East Java. The inclusion criteria were nurses and physician in Community-Integrated Health Care. The respondents were assessed using the Abilities of Health Care Workers Checklist pre-treatment and post-treatment. The outcomes were analyzed using the Wilcoxon signed rank test. There was a significant increased in the abilities of health care workers to provide psychiatric services after treatment (p<0.05). The liaison psychiatric services were considered to be effective in increasing the abilities of health care workers in improving the treatment of HIV/AIDS.